KEEFEKTIFAN SEKOLAH, FUNGSI DAN MODEL - Teguh Sihono; Norlia Binti Mat Norwani (Universitas Negeri Yogyakarta, 2010)
School functions are created forthe learner’s reproduction of knowledge, attitudes, values, and techniques that have a culture. There are five types of school function: engineering/economic function, political function, human/social function, cultural function, and educational function. Each type of the school function operates at five levels (individual, institution, community, society, and international). The effectiveness of a school is the capacity of the school to maximize its functions or the extent to which the school can perform the functions which consists of five types: technical/economic, human/social, political, cultural, and educational. The effectiveness of the school shows effective school performance in order to improve the quality of education. There are eight models of school effectiveness that places emphasis on each different aspect to the dynamic process of the school in an effective struggle for survival. The models are: the model of destination; input source model; process model; satisfaction model; legitimacy model; ineffectiveness model, organizational learning model, and total quality management (TQM) models. In maximizing the school’s function, school administrators can choose among the eight models of school effectiveness, in accordance with the interests, needs and condition of each school. Keywords: Effectiveness, Function, Model